TRANSITION FROM MANAGED FLOATING TO FEARLESS FLOATING UNDER THE FEAR OF FLOATING IN EMERGING MARKET COUNTRIES (Third Sector Social Economic Review, 2020)
In the wake of 1990s and 2000s, the main view was that flexible exchange rates were successful in absorbing domestic and international shocks under free capital mobility, and the inflation targeting strategy was directed to the central bank in developing countries to follow a counter-cyclical independent monetary policy. it provides the opportunity. Another implication from these crises is that intermediate regimes, which are called hard pegs or soft pegs, are vulnerable to financial crises. However, this traditional view is under intense criticism with the increasing financial integration in the world economy. Criticisms made to the traditional approach are grouped under three headings. The first of these criticisms is that there is no shift towards more flexible exchange rate regimes in the world economy. The second is that the impossible trinity hypothesis, accepted as the paradigm of the open economy, causes a dilemma in developing countries. The third criticism is on the effectiveness of exchange rate interventions. The conclusion from these criticisms is that developing countries should “invest” in the floating exchange rate regime so that they can fluctuate fearlessly.
Keywords: Floating Exchange Rates; Impossible Trinity; Fear of Floating; Impossible Duo